A systematic breakdown of the levels of evidence supporting the European Society of Cardiology guidelines. (29th August 2020) - van Dijk, Wouter B; Grobbee, Diederick E; de Vries, Martine C; Groenwold, Rolf H H; van der Graaf, Rieke; Schuit, Ewoud
Abstract: Aims: Reviews of clinical practice guidelines have repeatedly concluded that only a minority of guideline recommendations are supported by high-quality evidence from randomised controlled trials. The aim of this study is to evaluate whether these findings apply to the whole cardiovascular evidence base or specific recommendation types and actions. Methods: All recommendations from current European Society of Cardiology guidelines were extracted with their class (I, treatment is beneficial; II, treatment is possibly beneficial; III, treatment is harmful) and level of evidence (A, multiple randomised controlled trials/meta-analyses; B, single randomised controlled trials/large observational studies; C, expert opinion/small studies). Recommendations were categorised by type (therapeutic, diagnostic, other) and actions (e.g. pharmaceutical intervention/non-invasive imaging/test). Results: In total, 3531 recommendations (median 128, interquartile range 108–150) were extracted from 27 guidelines. Therapeutic recommendations comprised 2545 (72.1%) recommendations, 411 (16.1%) were supported by level of evidence A, 833 (32.7%) by B and 1301 (51.1%) by C. Class I/III (should/should not) recommendations on minimally invasive interventions were most supported by level of evidence A (55/183, 30.1%) (B [70/183, 38.3%], C [58/183, 31.7%]), while class I/III recommendations on open surgical interventions were least supported by level of evidence A (15/164, 9.1%) (B [34/164, 20.7%], C [115/164, 70.1%]). Of all (831, 23.5%) diagnostic recommendations, just 44/503 (8.7%) class I/III recommendations were supported by level of evidence A (B (125/503, 24.9%), C (334/503, 66.4%)). Conclusion: Evidence levels supporting European Society of Cardiology guideline recommendations differ widely between recommendation types and actions. Attributing to this variability are different evidence requirements, therapeutic/diagnostic recommendations, different feasibility levels for trials (e.g. open surgical/pharmacological) and many off-topic/policy recommendations based on expert opinion.